Model Media Interaktif Articulate Storyline Untuk Menumbuhkan Kemandirian Membaca Permulaan Peserta Didik SD - Yuni Yati; Sutama Sutama; Markhamah Markhamah (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Obstacles that occur when teaching early reading in low grades are the lack of media used to help students learn to read and the lack of human resources in the use of technological devices, especially in the current pandemic era. This study aims to develop an Android-based interactive learning media for beginning reading with the help of Articulate Storyline software and determine the feasibility of the learning media. The method used is the Research & Development (R&D) method. The data collection technique was done through a questionnaire, the research instrument used a questionnaire sheet. This study resulted in Android-based applications and products assessed from the feasibility of using media as measured by the quality of content and objectives and instructional quality. Assessors are conducted by peers, on the assessment of the quality of content and objectives, the assessor states that the learning media is in the appropriate category, and based on the instructional quality assessment questionnaire on the trial, the learning media is also declared to be in the appropriate category so that the learning media can be used to assist the learning process.